Deleting myeloid IL-10 receptor signalling attenuates atherosclerosis in LDLR-/- mice by altering intestinal cholesterol fluxes - Lauran Stöger, J.; Boshuizen, Marieke C. S.; Brufau, Gemma; Gijbels, Marion J. J.; Wolfs, Ine M. J.; van der Velden, Saskia; Pöttgens, Chantal C. H.; Vergouwe, Monique N.; Wijnands, Erwin; Beckers, Linda; Goossens, Pieter; Kerksiek, Anja; Havinga, Rick; Müller, Werner; Lütjohann, Dieter; Groen, Albert K.; de Winther, Menno P. J. (Thrombosis and Haemostasis, 2016)
Inflammatory responses and cholesterol homeostasis are interconnected in atherogenesis. Interleukin (IL)-10 is an important anti-inflammatory cytokine, known to suppress atherosclerosis development. However, the specific cell types responsible for the atheroprotective effects of IL-10 remain to be defined and knowledge on the actions of IL-10 in cholesterol homeostasis is scarce. Here we investigated the functional involvement of myeloid IL-10-mediated atheroprotection. To do so, bone marrow from IL-10 receptor 1 (IL-10R1) wild-type and myeloid IL-10R1-deficient mice was transplanted to lethally irradiated female LDLR-/- mice. Hereafter, mice were given a high cholesterol diet for 10 weeks after which atherosclerosis development and cholesterol metabolism were investigated. In vitro, myeloid IL-10R1 deficiency resulted in a pro-inflammatory macrophage phenotype. However, in vivo significantly reduced lesion size and severity was observed. This phenotype was associated with lower myeloid cell accumulation and more apoptosis in the lesions. Additionally, a profound reduction in plasma and liver cholesterol was observed upon myeloid IL-10R1 deficiency, which was reflected in plaque lipid content. This decreased hypercholesterolaemia was associated with lowered very low-density lipoprotein (VLDL) and low-density lipoprotein (LDL) levels, likely as a response to decreased intestinal cholesterol absorption. In addition, IL-10R1 deficient mice demonstrated substantially higher faecal sterol loss caused by increased non-biliary cholesterol efflux. The induction of this process was linked to impaired ACAT2-mediated esterification of liver and plasma cholesterol. Overall, myeloid cells do not contribute to IL-10-mediated atheroprotection. In addition, this study demonstrates a novel connection between IL-10-mediated inflammation and cholesterol homeostasis in atherosclerosis. These findings make us reconsider IL-10 as a beneficial influence on atherosclerosis.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Interleukin-10; myeloid cells; atherosclerosis; cholesterol; TICE